ANALISIS ASPEK SHARIA COMPLIANCE DARI PEMBIAYAAN TAKE OVER PADA PERBANKAN SYARIAH - Iskandar Iskandar; Ilva Andira (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2018)
This is rechecked by BI Checking trade checking andreassessment of guarantee application about take over of islamic baking. Then he submit a financing proposals to the FC. Which is given to financing committee, the next step is making a card counteracts and fund disbursement then the bank. Settle the client’s debt from the previous bank .in conducting its business The Bank and Brand Banda Aceh must comply with the principles of Sharia or Compliance Sharia. In conducting this take-over financing, Islamic Banks can use several contracts stipulated by fatwa No. 31/DSN-MUI/IV/2001 about Debt Transfer. Regarding aspectsof sharia complianceon take-over financing at PT. Islamic banking Brand Banda Aceh is really guarded by the bank, except, the initial financing is KPR financing because it is difficult to know that the building that is standing is being renovated or building from the beginning and if the funds provided for business capital financing are clear the financing is from the turnover of goods which can be seen directly from the store. Keywords: Take Over Financing, Sharia Compliance